2010
DOI: 10.1007/s10552-010-9622-6
|View full text |Cite
|
Sign up to set email alerts
|

Tea and coffee intake in relation to risk of breast cancer in the Black Women’s Health Study

Abstract: Prospective studies of tea and coffee intake and breast cancer risk have yielded inconsistent results. None of these studies has reported separately on African-American women. We prospectively examined the relation of tea and coffee consumption to risk of breast cancer among 52,062 women aged 21 to 69 at enrollment in 1995 in the Black Women’s Health Study. Dietary intake was assessed in 1995 and 2001 using a validated food frequency questionnaire. Cox proportional hazards models were used to estimate incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 39 publications
3
57
1
Order By: Relevance
“…Caffeine intake also presented a result lower than the findings of Boggs et al 43 in a prospective cohort study in which the median intake was 312 mg/day, while in our findings, this intake was 108.11 mg/day. In a study conducted in Brazil among both white and black men, higher calcium intake was found in whites (720 ± 346 versus 558 ± 236 mg), but there was only a correlation with the bone mineral density of the femoral neck among blacks.…”
contrasting
confidence: 99%
“…Caffeine intake also presented a result lower than the findings of Boggs et al 43 in a prospective cohort study in which the median intake was 312 mg/day, while in our findings, this intake was 108.11 mg/day. In a study conducted in Brazil among both white and black men, higher calcium intake was found in whites (720 ± 346 versus 558 ± 236 mg), but there was only a correlation with the bone mineral density of the femoral neck among blacks.…”
contrasting
confidence: 99%
“…Additionally, our population primarily comprised white women, and our findings may not be generalizable to other racial/ethnic groups. However, although the prevalence of risk factors often differs across population subgroups, many breast cancer risk factors have been documented to operate across racial/ethnic groups, as would be expected from diseases with a common underlying biology (20,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Although we included family history as a nonmodifiable risk factor, we did not directly test for inherited mutations in genes that increase the risk of breast cancer; these are more common causes of breast cancer in younger, premenopausal women (53).…”
Section: Discussionmentioning
confidence: 99%
“…35 Conversely, the HANDLS African American population was about three times below the national average. In a study by Boggs et al, 36 it was noted that African American females drink less tea and coffee than their white counterparts do. When expressed as caffeine (in mg) per kilogram of body weight, the caffeine intake of the African Americans was lower than that reported by Mitchell et al…”
Section: Caffeine Intakesmentioning
confidence: 97%